2020
DOI: 10.1016/j.adengl.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Medicolegal aspects of teledermatology

Abstract: Teledermatology has facilitated specialist care during the crisis caused by the coronavirus disease 2019 pandemic, eliminating unnecessary office visits and the possible exposure of patients or dermatologists. However, teledermatology brings forward certain ethical and medicolegal questions. A medical consultation in which the patient is not physically present is still a medical act, to which all the usual ethical and medicolegal considerations and consequences apply. The patient’s right to autonomy and privac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…5,6 Telemedicine has been used in almost every specialty, including procedural specialties. 5,[7][8][9][10][11][12][13][14][15][16][17] Further, especially since the beginning of the COVID-19 pandemic, telemedicine use has increased internationally. [18][19][20][21] Although various forms of telemedicine, including phone calls and electronic messaging, have been used extensively in our clinic for years, the COVID-19 pandemic has led to the implementation and successful use of audiovisual technologies for patient care visits across the Mayo Clinic enterprise.…”
mentioning
confidence: 99%
“…5,6 Telemedicine has been used in almost every specialty, including procedural specialties. 5,[7][8][9][10][11][12][13][14][15][16][17] Further, especially since the beginning of the COVID-19 pandemic, telemedicine use has increased internationally. [18][19][20][21] Although various forms of telemedicine, including phone calls and electronic messaging, have been used extensively in our clinic for years, the COVID-19 pandemic has led to the implementation and successful use of audiovisual technologies for patient care visits across the Mayo Clinic enterprise.…”
mentioning
confidence: 99%
“… 66 Furthermore, there is a need for internationally shared guidelines to address certain medico-legal shortcomings, such as the absence of informed consent for teledermatology patients and the risk of loss of privacy of patients. 67 To date, the advancement of technologies has led to the development of AI, with devices that can express human capabilities, including reasoning and decision-making. Several studies have shown, however, that at present no programme, despite advanced, can replace a dermatological examination, not least because of the absence of datasets that need to be supplemented by the dermatologists themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown, however, that at present no programme, despite advanced, can replace a dermatological examination, not least because of the absence of datasets that need to be supplemented by the dermatologists themselves. 67 It also raises ethical and medico-legal issues that need to be addressed at an international level. 68 …”
Section: Discussionmentioning
confidence: 99%
“…Teledermatology provides specialized medical care with reduced diagnostic precision and a more significant proportion of incorrect diagnoses. As a result, given that it is a new technique, it should be used with extreme caution concerning illnesses with lower diagnostic accuracy [26], such as inflammatory dermatoses and skin cancers, has been indicated. Teledermatology must defend the patient's right to autonomy, professional privacy, confidentiality, and intimacy.…”
Section: Table 1: Various Studies Assessing Teledermatology For Educa...mentioning
confidence: 99%
“…The doctor must have direct knowledge of the patient's clinical history or have access to it during medical care to safeguard the patient's privacy and intimacy and the doctor-patient relationship. The method of telecare used to conduct the consultation, the suggestions, and the recommended medical care should all be written in the patient's medical file [26]. An information method on the goals and uses of the images captured and sent is necessary for the practice of teledermatology.…”
Section: Table 1: Various Studies Assessing Teledermatology For Educa...mentioning
confidence: 99%